Acessibilidade, barreiras e superação: estudo de caso de experiências de estudantes com deficiência na educação superior - Silva, Jackeline Susann Souza da (2014)
8 ABSTRACT In this century, worldwide, the theme of accessibility became an important guideline for governments and institutions to ensure the rights of people with disability to education, work, culture and leisure, and to improve their quality of life and participation in the mainstream. This involves the elimination of barriers in institutional settings, including higher education institutions, which have been historically selective and elitist. There are few studies showing how attitudinal, physical, informational-communicational, and pedagogical-curricular barriers are built and how students with disability meet and overcome them in order to have success in higher education. Therefore, this study focuses on the following question: How students with disability experience accessibility in higher education? From a cultural studies perspective, it aims to identify and analyze their experiences of accessibility (or not) at entrance examinations (access), during preparation until graduation (permanence and acquisition). A case study methodology, combined with the shadowing technique, was used to investigate the experiences of accessibility of six students (three male and three female) at Federal University of Paraíba, João Pessoa campus, in Brazil. Main findings show that: (a) accessibility is an issue that should be addressed prior to university entrance because there is a set of barriers that prevent access of people with disability, concerning information about graduate degrees and enrolment in entrance examinations, family social and economic situation, program choice; (b) both the federal government and the university are very slowly in moving towards an institutional policy of effective inclusion, and there is no monitoring or assessment procedures for the inclusion program in place (Programa Incluir), so there are still tough barriers for this group; (c) different types of accessibility are interdependent and mutually reinforcing, however attitudinal barriers seem to be the most relevant because when there is attitudinal access, in the first place, the other barriers tend to be reduced or eliminated; (d) in spite of the legal framework, higher education students with disability still know it superficially, or lack appropriate knowledge about their rights, and rarely use the existing legal system to ensure them. Their inner strength and the support arrangements which they develop on their own are what allow them to persist and accomplish their qualification in order to have better employment chances.